The supreme audit institution in the Republic of North Macedonia – two decades of building public trust - Dionisijev, Ivan; Bozhinovska Lazarevska, Zorica; Trpeska, Marina; Atanasovski, Atanasko (Journal of Public Budgeting, Accounting & Financial Management, 2022)
Purpose – The state audit is crucial for society in ensuring the transparent and legal spending of public funds. In the Republic of North Macedonia, although state audit-related activities have existed since the state’s independence, the State Audit Office started operating as a Supreme Audit Institution in 1999. The purpose of this research was to explore the development of the State Audit Office in the Republic of North Macedonia over the past two decades regarding the organisational aspect and the state audit-related activities. Design/methodology/approach – The research is based on a detailed analysis performed using statistical tests of data collected from the State Audit Office’s annual reports on operation and performed audits in the period 2001–2020, concerning the budget, organisational size, audit engagements, audited public revenues and expenditures, audit reports, and given recommendations and their implementation. The survey method was used to determine other factors that could have a correlation with the development of the State Audit Office. Findings – In general, it can be concluded that the State Audit Office has grown in terms of financial resources at its disposal and the organisational size (number of employees). Although there is no correlation between the regularity audit engagements and the audited public revenues and expenditures, there is still a positive correlation between the audited public revenues and expenditures. The implementation of the given recommendations by the auditors is not related to the number of recommendations in the final audit reports. There are several internal, external and international factors that have a positive correlation with the development of the State Audit Office. Research limitations/implications – The first limitation of this paper pertains to the period of existence of the Supreme Audit Institution in the Republic of North Macedonia not being very long in order to be able to draw more significant conclusions. The second limitation concerns the measurement of the variables from the survey being based only on the perception of the state auditors. Such a measurement method might be considered less accurate in describing the actual situation. Originality/value – To the best of our knowledge, this paper is the only one that explores the development of the Supreme Audit Institution in the Republic of North Macedonia. Furthermore, it provides a good basis for further detailed research on areas relevant to the issue. We believe that this research will enrich the existing body of literature on state audit by offering a concrete example of the development of a Supreme Audit Institution in a less-researched geographical area.
Keywords: State audit; Supreme audit institution; State audit office; Development; North Macedonia